CLIENT CENTRED KONSELING DALAM PENCEGAHAN RELAPSE PENGGUNA NAPZA USIA PRODUKTIF DI LKS ATAP LANGIT - hidayat, Nur (Fakultas Dakwah dan Komunikasi Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Abstract: This research is motivated by the importance of counselling to clients who use drygs who still frequently exprience relapses. If not handled properly, then the clients have the potential to repeat their habit of using illegal drugs. The research problem is how the process of implementing counseling services throught a client centered approach at LKS Atap Langit and the obstacles in implementing these counseling services.this type of research is field research which is analyzed using qualitative descriptive methods. The data collection methods used in this study were observation, interview, and documentation related to the reseacrh conducted. It can be concluded that the implementation of counseling though a client centered approach in the preventing relapse of productive age drug users at LKS Atap Lamgit is very effective for clients who are of productive age. Efforts made by the head of the foundation, counselor, psychologist, and psychiatrist in this prevention are counseling services through a client centered approach. The counseling service provided by the counselor is that there are six stages that the client must go through with a schedule of 4 meetings in one month (once a week) and carried out for 2-3 months, depending on the severity of the user. In addition, there are several obstacles in the process of implementing this counseling which are divided into two types, namely internal and external Barriers from the internal side such as client closure, family counseling is difficult to apply, and the pandemic period. Then the obtacles from the external side are the client’s economic barriers, erratic weather factor, and not having transportation. Keywords: Counseling, Client Centered, Relapse, Productive age, drugs Abstrak: Penelitian ini dilatarbelakangi karena pentingnya konseling kepada klien pengguna NAPZA yang masih sering mengalami kambuh (relapse). Adapun permasalahan penelitian adalah bagaimana proses pelaksanaan layanan konseling melalui pendekatan client centered di LKS Atap Langit. Jenis penelitian ini adalah penelitian lapangan (field research) yang dianalisis dengan menggunakan metode deskriptif kualitatif. Metode pengumpulan data yang digunakan dalam penelitian ini ialah observasi, wawancara, dan dokumentasi terkait penelitian yang dilakukan. Tujuan penilian ini dalah untuk mengetahui penerapan client centered konseling dalam pencegahan relapse pengguna NAPZA. Hasil dari penelitian ini adalah sangat efektif diterapkan bagi klien yang tergolong usia produktif. Upaya yang dilakukan oleh ketua yayasan, konselor, psikolog, dan psikiatri dalam pencegahan ini yaitu dengan layanan konseling melalui pendekatan client centered. Layanan konseling yang diberikan konselor ialah ada enam tahapan yang harus dilalui klien dengan jadwal 4 kali pertemuan dalam satu bulan (satu minggu sekali) dan dilakukan selama 2-3 bulan, tergantung dari tingkat keparahan pengguna. Kata Kunci: Konseling, client centered, relapse, usia produktif, NAPZA.